2019
DOI: 10.1038/s41598-019-45881-x
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged use of noninvasive positive pressure ventilation after extubation among patients in the intensive care unit following cardiac surgery: The predictors and its impact on patient outcome

Abstract: This retrospective, observational cohort study aimed to determine the independent risk factors and impact of prolonged non-invasive positive pressure ventilation (NIPPV) after extubation among patients in the intensive care unit following cardiac surgery. Patients who received prophylactic NIPPV after extubation were categorized into prolonged (NIPPV duration >3 days, n = 83) and non-prolonged groups (NIPPV duration ≤3 days, n = 105). The perioperative characteristics and hospital outcomes were recorded. The m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 46 publications
(54 reference statements)
0
6
0
Order By: Relevance
“…2 Recent literature shows that the incidence of complications in patients undergoing CS is relatively frequent, with a range of 15% to 30%. 3 Notably, patients often encounter complications such as significant pulmonary dysfunction postoperatively, 4 haemorrhage, stroke, and delirium, 5,6 for which they often remain under-diagnosed. Depending on the methodology, post-CS delirium is diagnosed in 26% to 52% of patients, with some studies reporting percentages as high as 70%.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…2 Recent literature shows that the incidence of complications in patients undergoing CS is relatively frequent, with a range of 15% to 30%. 3 Notably, patients often encounter complications such as significant pulmonary dysfunction postoperatively, 4 haemorrhage, stroke, and delirium, 5,6 for which they often remain under-diagnosed. Depending on the methodology, post-CS delirium is diagnosed in 26% to 52% of patients, with some studies reporting percentages as high as 70%.…”
Section: Introductionmentioning
confidence: 99%
“…Cardiac surgery (CS) involves several challenges, both for the patients and the health care providers, 1‐3 such as frequent incidence of complications, postoperative complications, and high nursing skills required. The high clinical complexity of patients undergoing CS is often associated with numerous complications 1 because of a combination of factors, including higher‐risk surgery, age of patients at the time of surgery, and the presence of comorbid conditions 2 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Contou et al [ 23 ] reported that the patients with PaCO 2 > 60 mmHg, compared with the patients with PaCO 2 ≤ 60 mmHg, required longer duration of NPPV treatment and LOS. However, Chen et al [ 24 ] reported 188 patients who received prophylactic NPPV after extubation, according to duration of NPPV treatment, were divided into prolonged (duration of NPPV treatment > 3 days) and non-prolonged groups (duration of NPPV treatment ≤ 3 days). The results made clear that compared with non-prolonged group, prolonged group significantly increased the risk of complications, prolonged ICU and hospital stay, but had no significant effect on mortality.…”
Section: Discussionmentioning
confidence: 99%
“…BUN is usually regarded as an important indicator of blood volume. Although many patients with DKA are complicated with acute renal failure, dehydration is the most common state among patients with DKA due to hypovolemia and hypotension Accepted Manuscript also revealed that high BUN levels are correlated with poor prognosis in ICU patients [24,25]. As high BUN was also found to be related to the poor prognosis of patients with acute heart failure, acute respiratory disease syndrome, and hepatic decompensation [26][27][28], BUN might reflect the degree of injury of multiple important organs, which were also found to be an important risk factor of critically ill patients.…”
Section: Accepted Manuscriptmentioning
confidence: 99%